Clinical and electrophysiological profiles of patients with diabetic peripheral neuropathy: A cross-sectional study of 50 patients. - Satapathy, Rajalaxmi; Dash, Prerana; Das, Pragateshnu (Student’s Journal of Health Research Africa, 2025)
Background: Diabetic peripheral neuropathy (DPN) is a prevalent complication of type 2 diabetes mellitus, often presenting with sensory and motor deficits. This study aimed to characterize the clinical and electrophysiological profiles of patients with DPN and explore correlations between symptom severity and nerve conduction parameters. Methods: A cross-sectional study was conducted at the Neurology Outpatient Department of a tertiary care centre of Eastern India. Fifty patients with type 2 diabetes and clinical signs of peripheral neuropathy were enrolled. The Neuropathy Disability Score (NDS) was used for clinical grading. Nerve conduction studies (NCS) of the peroneal, tibial, and sural nerves were performed. Results: Sensory symptoms were predominant (84%), with sensorimotor involvement in 16%. Patients with higher NDS scores showed significantly reduced sural SNAP and peroneal CMAP amplitudes. A strong inverse correlation was observed between NDS and sural SNAP amplitude (r = –0.68, p < 0.001) and peroneal conduction velocity (r = –0.55, p = 0.002). Sural nerve abnormalities were present in 90% of patients. Conclusion: Electrophysiological parameters, particularly sural SNAP amplitude, correlate strongly with clinical severity in DPN. Combined use of NDS and NCS enhances early detection and stratification of neuropathy severity. Recommendations Adopt Combined Screening Protocols: Integrate NDS scoring with targeted NCS, especially sural SNAP amplitude, as a routine diagnostic approach in diabetic clinics. This dual assessment can improve early detection and stratification of DPN severity.